Numerical evaluation of the bearing capacity factor N'c of circular and ring footings. Issue 1 (2nd January 2017) - Remadna, Mohamed S.; Benmebarek, Sadok; Benmebarek, Naima
ABSTRACT: Ring footings are widely used to support structures like silos and storage tanks. Analytical design of safe and economical shallow footings requires the knowledge of the bearing capacity factors N'c and N'γ . The geotechnical design Eurocode 7 provides such factors only for simple geometric shapes like squares, circles or rectangles. Furthermore the N'γ factor has been extensively carried out but the research on the N'c factor hasn't yet been performed. Thus, the present study aims to provide the first numerical N'c values of a ring footing laying on general c-φ Mohr-Coulomb soil. The results, carried out by using FLAC code, indicate that for rough footings there is an optimal ring which is also dependent of the friction φ. The optimal value of ri /r0 is found to be almost equal to 0.26, 0.33 and 0.46 corresponding respectively to a low, medium and high friction soil. The results also indicate that the soil dilation angle influences the value of N'c when the soil displays high non-associativity for large internal friction angle values. The computational results are presented in the form of design tables and graphs, and compared with previous published results available in the literature.